From Protests to Progress: Unlocking the Potential of the Nigerian Youth for Political Reform (British Journal of Multidisciplinary and Advanced Studies, 2024)
In light of persistent political challenges and social unrest in Nigeria, this paper examines the transformative potential of the nation's youth, whose rich history of activism has significantly shaped the country's political landscape. However, despite these historical precedents, contemporary youth engagement remains crucially significant, particularly in light of recent protests that have reverberated across the nation. By examining the historical context of youth activism in Nigeria, this paper elucidates the evolution of past movements and their enduring impact on the country’s political sphere. Furthermore, the paper analyses the contemporary landscape of youth engagement, highlighting the multifaceted nature of recent protests and the underlying catalysts driving them. Of particular significance is the role of social media in mobilizing Nigerian youth, providing a platform for collective action, and amplifying their voices in the public discourse. Despite the undeniable agency demonstrated by Nigerian youth, numerous barriers impede their ability to effect lasting political reform.  In response, this paper proposes a strategic framework for empowering Nigerian youth for leadership, encompassing initiatives such as education and awareness campaigns, the creation of spaces for youth representation in government, and the strengthening of youth-led organizations. In conclusion, this paper advocates for sustained attention and investment in empowering Nigerian youth as catalysts for political reform. Recognizing their agency and potential, stakeholders must work collaboratively to foster an environment conducive to meaningful youth engagement and inclusive governance.